x2+6x-100=0

Use the quadratic formula to find the solutions.

-b±b2-4(ac)2a

Substitute the values a=1, b=6, and c=-100 into the quadratic formula and solve for x.

-6±62-4⋅(1⋅-100)2⋅1

Simplify the numerator.

Raise 6 to the power of 2.

x=-6±36-4⋅(1⋅-100)2⋅1

Multiply -100 by 1.

x=-6±36-4⋅-1002⋅1

Multiply -4 by -100.

x=-6±36+4002⋅1

Add 36 and 400.

x=-6±4362⋅1

Rewrite 436 as 22⋅109.

Factor 4 out of 436.

x=-6±4(109)2⋅1

Rewrite 4 as 22.

x=-6±22⋅1092⋅1

x=-6±22⋅1092⋅1

Pull terms out from under the radical.

x=-6±21092⋅1

x=-6±21092⋅1

Multiply 2 by 1.

x=-6±21092

Simplify -6±21092.

x=-3±109

x=-3±109

Simplify the numerator.

Raise 6 to the power of 2.

x=-6±36-4⋅(1⋅-100)2⋅1

Multiply -100 by 1.

x=-6±36-4⋅-1002⋅1

Multiply -4 by -100.

x=-6±36+4002⋅1

Add 36 and 400.

x=-6±4362⋅1

Rewrite 436 as 22⋅109.

Factor 4 out of 436.

x=-6±4(109)2⋅1

Rewrite 4 as 22.

x=-6±22⋅1092⋅1

x=-6±22⋅1092⋅1

Pull terms out from under the radical.

x=-6±21092⋅1

x=-6±21092⋅1

Multiply 2 by 1.

x=-6±21092

Simplify -6±21092.

x=-3±109

Change the ± to +.

x=-3+109

x=-3+109

Simplify the numerator.

Raise 6 to the power of 2.

x=-6±36-4⋅(1⋅-100)2⋅1

Multiply -100 by 1.

x=-6±36-4⋅-1002⋅1

Multiply -4 by -100.

x=-6±36+4002⋅1

Add 36 and 400.

x=-6±4362⋅1

Rewrite 436 as 22⋅109.

Factor 4 out of 436.

x=-6±4(109)2⋅1

Rewrite 4 as 22.

x=-6±22⋅1092⋅1

x=-6±22⋅1092⋅1

Pull terms out from under the radical.

x=-6±21092⋅1

x=-6±21092⋅1

Multiply 2 by 1.

x=-6±21092

Simplify -6±21092.

x=-3±109

Change the ± to -.

x=-3-109

x=-3-109

The final answer is the combination of both solutions.

x=-3+109,-3-109

The result can be shown in multiple forms.

Exact Form:

x=-3+109,-3-109

Decimal Form:

x=7.44030650…,-13.44030650…

Solve Using the Square Root Property x^2+6x-100=0